Satellite cells and myonuclei in long‐term denervated rat muscles - de Castro Rodrigues, Antonio [UNESP] (1995)
Background: The percentage of satellite cells rapidly decreases in aneurally regenerating soleus muscles of rat. Also denervation of intact muscles causes fiber loss and regeneration, but the fate of satellite cells is unknown; myonuclei have been suggested to undergo changes resembling those in apoptotic cells. Methods: Rat soleus and extensor digitorum longus (EDL) muscles were denervated at birth or at age 5 weeks and investigated after periods of up to 38 weeks. At least 400 myonuclei in each muscle were assessed by electron microscopy, and satellite cell nuclei were counted. In sity nick translation and tailing were performed after 30 weeks denervation in order to demonstrate DNA breaks associated with apoptosis. Results: Myotubes indicating regeneration were prominent in the adult denervated soleus and deep layers of EDL muscles after 7 weeks and in the superficial parts of EDL muscle after 16 weeks. The percentage of satellite cell nuclei slowly decreased to less than one fifth of normal after 20–30 weeks. Almost all satellite cells had vanished 10 weeks after neonatal denervation. Degenerating myonuclei in adult, but not in neonatally denervated muscles, remotely resembled apoptotic nuclei of lymphocytes, but no evidence of DNA breaks was found. Conclusion: Denervation of rat skeletal muscles causes, in addition to fiber atrophy, loss of fibers with subsequent regeneration. Proliferation of satellite cells under aneural conditions may lead to exhaustion of the satellite cell pool. This process is more rapid in growing than in adult muscles. Myonuclei in denervated muscles do not show DNA breaks which can be demonstrated by in situ nick translation. © 1995 Wiley‐Liss, Inc. Copyright © 1995 Wiley‐Liss, Inc.